EDUCATION PSYCHOLOGICAL UNDERSTANDING ON MADRASAH IBTIDAIYAH EDUCATORS IN BANTUL - Aninditya Sri Nugraheni; sugiharto sugiharto (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2017)
Education world cannot be separated from psychology of education. Scholarly relevant to psychology of education is crucial to be understood by each educator. However, seeing the existing phenomena, there are many educators who lack of comprehension on it. The researcher finds discrepancy between the educator’s action and the existing psychological theory. Learners deserve and have to obtain skill and science which are appropriate with their age. Therefore, the researcher conduct a research towards educators on the understanding in psychology of education concerning reading and writing skill for learners in Primary School/MI age. Based on the research conducted by the researcher, data which is obtained by four private MIs by using interview towards 25 educators who are scholars, it can be drawn a conclusion that most of them have not comprehended the skill which is appropriate with Primary School/MI learners of 1st grade. For instance, they agree to carry out reading and writing test as the requirement to register the Primary School/MI which is 70%. It is discussed in Act Number 20 Year 2003 on National Education System. On Paragraph 3 of Article 69, it is mentioned that Learners Admissions of 1st grade of Primary School/MI or other equal school is not based on the result of reading, writing, calculating and other types of test. Furthermore, concerning learners’ readng and writting skill of certain age, 75% of them answer in the end of childhood period, 20% of them answer in the beginning of 1st grade and the others, which is 5% of them answer in the beginning of 1st grade or ahead of the second grade. 5% of them asnwer on the period between the first and second grade. It indicates the need of government’s socialization associated with psychology of education towards educators.